Coping on the inside: Design for therapeutic incarceration interventions - A case study. - Wagenfeld, Amy; Winterbottom, Daniel (Work, 2021)
BACKGROUND: Adjusting to incarceration is traumatic. An under-utilized strategy understood to buffer and counteract the negative impacts of incarceration are nature interventions. OBJECTIVE: Outcomes of an interdisciplinary design studio course focused on developing masterplans for a women's prison in the Pacific Northwest (US) are presented. Course objectives included comprehension and application of therapeutic and culturally expressive design principles to increase the benefits of environmental design within a carceral setting; collaboration, developing a deeper, more representative understanding of how design processes can improve the lives of marginalized populations; and enhancing design skills, including at masterplan and schematic scale using an iterative process and reflection. METHODS: A landscape architect, occupational therapist, and architect teaching team, with support from architects and justice specialists facilitated an elective design studio course to redesign the Washington Corrections Center for Women campus. RESULTS: In a ten-week academic quarter, six student design teams created conceptual masterplans for therapeutic outdoor spaces at the Washington Corrections Center for Women. Students presented their plans to prison staff, current and ex-offenders, and architects and landscape architects in practice, and then received positive feedback. CONCLUSION: Despite well-documented need for and value of nature interventions to improve health and wellbeing for everyone regardless of circumstance or situation, the project awaits administrative approval to move forward to installation.